PENGARUH KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE OPPO: (Studi Kasus : Mahasiswa Prodi Manajemen Fakultas Ekonomi Universitas Katolik Santo Thomas Medan) - Simangunsong, Elisabeth; Sitanggang, Darna (UNIKA Santo Thomas, 2023)
The purpose of this study was to determine the effect of brand trust consisting of brand predictability, brand liking, brand competence, brand reputation and trust in the company partially and simultaneously on purchasing decisions for Oppo mobile phones. The number of samples is 96 respondents. Multiple linear regression analysis technique and to test the hypothesis used t and F test. The results showed that respondents' responses regarding: brand predictability were more dominant stating the predictability of the brand owned by Oppo cellphones was very good, brand competence was more dominant indicating brand competence owned by Oppo cellphones had been well developed, brand preference was more dominant in expressing preference for the brand owned. Oppo cellphones are good, Reputation is more dominant stating that the brand reputation owned by Oppo cellphones is very good, Trust in the company is more dominant stating that trust in the company owned by Oppo cellphones is very good and Purchasing decisions are more dominant stating that purchasing decisions owned by Oppo cellphones are in accordance with need . The t-test and F-test values show that the variables of brand predictability, brand preference, brand competence, brand reputation and trust in the company have a partially and simultaneously significant influence on the purchasing decision of Oppo mobile phones. The correlation coefficient value of brand predictability variables, brand preference, brand competence, brand reputation and trust in the company to brand loyalty has a strong relationship of r = 0.954a. While the coefficient of determination is 0.897, which means that the variables of brand predictability, brand preference, brand competence, brand reputation and trust in the company are able to explain 89.7% of the decision to buy Oppo mobile phones while 10.3% is influenced by other factors. Oppo mobile phone manufacturers should increase brand predictability variables, brand liking, brand competence, brand reputation and trust in the company so that they have more influence on purchasing decisions for Oppo mobile phones. This can be proven by the value of the regression coefficient which is much lower than the variable trust in the brand and brand reputation